An investigation of safety climate in OHSAS 18001-certified and non-certified organizations. Issue 3 (2nd July 2016) - Ghahramani, Abolfazl
Abstract : Many organizations worldwide have implemented Occupational Health and Safety Assessment Series (OHSAS) 18001 in their premises because of the assumed positive effects of this standard on safety. Few studies have analyzed the effect of the safety climate in OHSAS 18001-certified organizations. This case–control study used a new safety climate questionnaire to evaluate three OHSAS 18001-certified and three non-certified manufacturing companies in Iran. Hierarchical regression indicated that the safety climate was influenced by OHSAS implementation and by safety training. Employees who received safety training had better perceptions of the safety climate and its dimensions than other respondents within the certified companies. This study found that the implementation of OHSAS 18001 does not guarantee improvement of the safety climate. This study also emphasizes the need for high-quality safety training for employees of the certified companies to improve the safety climate.